Pengaruh Fasilitas dan Sosial Media Marketing Terhadap Keputusan Berkunjung Wisata Rumah Ladang Pamah Simelir Desa Telagah Kecamatan Sei Bingai - Sitepu, Karda Sitepu; Tarigan, Eka Dewi Setia; Nasution, Amrin mulia (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Tourism is a strategic sector in driving regional economic growth, so destination management needs to consider factors that influence tourist visitation decisions. This study aims to analyze the effect of facilities and social media marketing on tourist visitation decisions at the Rumah Ladang Pamah Simelir tourist attraction in Telagah Village, Sei Bingai District, Langkat Regency. This study uses a quantitative approach with an associative research design. The research sample consisted of 100 respondents selected using accidental sampling. Data collection was conducted through a questionnaire with a Likert scale, while data analysis used validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis with the help of SPSS. The results showed that facilities had a positive and significant effect on tourist visit decisions at the Rumah Ladang Pamah Simelir tourist attraction in Telagah Village, Sei Bingai District, Langkat Regency. Social media marketing was also proven to have a positive and significant effect on the decision to visit. Simultaneously, facilities and social media marketing had a significant effect on tourists' decision to visit. This study concluded that improving the quality of facilities and effective social media marketing management can encourage an increase in tourists' decision to visit. Therefore, tourism managers are advised to continue to develop facilities and digital marketing strategies in a sustainable manner.